A curious case of property privatization: two examples of the tragedy of the anticommons in Ho Chi Minh City-Vietnam. Issue 1 (2nd January 2017) - Nguyen, Thanh Bao; Van de Krabben, Erwin; Samsura, D. Ary A.
ABSTRACT: This paper focuses on the influence of land and property privatization processes on urban development in Ho Chi Minh City (HCMC), Vietnam. Many scholars have recognized that the privatization policy regarding property and land use rights may create a fragmentation of private land ownership, which eventually can lead to what has been called the tragedy of the anticommons . This paper observes how this phenomenon has also threatened urban development in HCMC after the introduction of the Doi Moi policy. Two case studies show two different types of development processes in HCMC, namely a small self-development project and a large-scale commercial project. Both case studies reveal how (potential) tragedies of the anticommons can be solved in different ways.